Implementation Multi-criteria Decision Making Technique in Overhaul Power Plants Projects - Parsa, Kia; Torfi, Fatemeh (International Journal of Economics and Financial Issues, 2017)
The aim of this study is to propose a multi-criteria decision making approach (MCDM) in order to evaluate Qualitative Factors in Overhaul Power Plants Projects, with due attention to the rating of qualitative criteria are considered as linguistic variables. Overhaul of the power generation plants affects the performance process. Some qualitative factors are of great importance in improving the quality of the process and avoiding wasting resources. The combined method of Analytic Network Process (ANP) and DEMATEL technique were used in this study. Four main and 16 secondary factors were identified in the final classification. Empirical results show that the proposed method is viable approaches in solving problem. When the performance ratings are vague and imprecise, this MCDM is a preferred solution method. The results show 8 highest Factors effects on the overhaul of the power plants respectively. Keywords: MCDM; ANP; DEMATEL; Overhaul. JEL Classification: O22